Odpowiedź:
[tex]a) \frac{2}{3}* \frac{1}{4} =\frac{1}{3} *\frac{1}{2} =\frac{1}{6} \\\frac{5}{8} *\frac{2}{5} =\frac{1}{4} *1=\frac{1}{4}[/tex]
[tex]b) \frac{1}{2}*\frac{5}{6} =\frac{5}{12} \\\frac{5}{6} *\frac{9}{10} =\frac{1}{2}*\frac{3}{2} =\frac{3}{4}[/tex]
[tex]c)\frac{3}{4}* 2\frac{1}{3} =\frac{3}{4} *\frac{7}{3} =\frac{1}{4}*7=\frac{7}{4} =1\frac{3}{4} \\3\frac{1}{3} *\frac{2}{10} =\frac{10}{3} *\frac{2}{10} =\frac{1}{3}*2 =\frac{2}{3}[/tex]
[tex]d)1\frac{2}{3} *1\frac{4}{5} =\frac{5}{3}*\frac{9}{5} =1*3=3\\2\frac{1}{4}* 1\frac{3}{5} =\frac{9}{4}*\frac{8}{5} =9*\frac{2}{5}=\frac{18}{5} =3\frac{3}{5}[/tex]